Made in China / produzido no polo industrial da zona franca de Manaus : o trabalho nas fábricas chinesas - Brito, Cleiton Ferreira Maciel (2017)
This research analyses the Chinese production in the Industrial Cluster of Manaus Free Zone, focusing on the production pattern and work management. In recent years, significant changes have been operating within the global production chain as a result of the massive displacement of Chinese capital towards the various regions of the globe. Brazil and, more specifically, the Amazon has been one of the main destinations of these Chinese investments. An empirical proof of these metamorphoses of global capital is the arrival of a set of Chinese factories at the Industrial Cluster of Manaus (PIM) from the beginning of the year 2000. In order to understand the meaning of this on the organization of local work, especially in relation to the process of productive restructuring developed in the last years, this research sought to organizationally map out four Chinese factories. Quantitative and qualitative data were produced and gathered together from workers, managers, managers of public and private institutions, and Chinese expatriates. The research findings show that the Chinese, on the one hand, incorporated the local production pattern but, on the other hand, reshaped labour management. Such remodelling I called "taylorization with Chinese characteristics", which operates under the duality of being, at the same time, Made in China, but Produced at the Industrial Cluster of Manaus. As a fundamental element of this process, it was observed that strong socio-productive linkages between parent-subsidiary generate fragile socio-productive links in the Industrial Cluster of Manaus, implying high control of the Manauara workforce and Chinese expatriates. In spite of this, there has been a process of "appropriateness / injunction" that causes some "Chinese characteristics" to be deepened while others have to undergo transformations.